Diagnosis and management challenges of in-stent restenosis in coronary arteries - Alraies, M Chadi (World J Cardiol, 2017)
Over the course of the 3 decades, percutaneous coronary intervention (PCI) with stent implantation transformed the practice of cardiology. PCI with stenting is currently the most widely performed procedure for the treatment of symptomatic coronary disease. In large trials, drug-eluting stents (DES) have led to a significant reduction in in-stent restenosis (ISR) rates, one of the major limitations of bare-metal stents. Due to these favorable findings, DES was rapidly and widely adopted enabling more complex coronary interventions. Nevertheless, ISR remains a serious concern as late stent complications. ISR mainly results from aggressive neointimal proliferation and neoatherosclerosis. DES-ISR treatment continues to be challenging complications for interventional cardiologists.